The Efficiency of the Market for Foreign Exchange Under Floating Exchange Rates - Cornell, W. Bradford; Dietrich, J. Kimball (The Review of Economics and Statistics, 1978)
W. Bradford Cornell, J. Kimball Dietrich, The Efficiency of the Market for Foreign Exchange Under Floating Exchange Rates, The Review of Economics and Statistics, Vol. 60, No. 1 (Feb., 1978), pp. 111-120